A cross-sectional study on beliefs about thirdhand smoke among the general population in Bangalore city, India - Chandran, Manjusha P.; M., Pramila; S., Geetha; Madhavan, Aswini; V., Akshay (International Journal Of Community Medicine And Public Health, 2022)
Background: Thirdhand smoke (THS) is a recently discovered health hazard which has become a public concern over the recent years due to its wide distribution in indoor environment and significant adverse biological and health ill effects. The “four R’s” that define the concept of THS include tobacco chemicals (some toxic) that remain, react, re-emit and/or are re-suspended long after active smoking ends. Harmful effects of active smoking and second-hand smoke were widely studied, however, only few studies were conducted on THS and its health effects. The aim of the study is to assess the beliefs about THS among the general population in Bangalore city, India Methods: This cross-sectional study used a structured multiple-choice questionnaire which incorporated the participant’s characteristics and the beliefs about THS (BATHS) scale. A sample size of 206 participants was obtained after study duration of 2 months. One-way ANOVA, student T test, generalized linear model and Pearson’s correlation were used for statistical analysis in SPSS version 22 software. Results: The test results showed a significant association between age (in years), gender, highest level of education, and smoking status with overall mean BATHS scale and subscales score. Pearson correlation analysis revealed the BATHS scale and its subscales scores to be interdependent. Conclusions: Older participants, females, participants who had a high level of education, and non-smokers were found to have higher knowledge regarding THS and its impact on health and persistence in the environment.